Atractivos turisticos del canton Mocache y su incidencia en el desarrollo economico, año 2019 - Tumbaco Inga, Bryan Alexander (2019)
The main objective of this research was to determine the relational incidence of tourist attractions in the local development of the Mocache canton of the Province of Los Ríos, variables of studies analyzed by other researchers previously but that have not left specific tools to establish established tourism products. a promotion methodology for visitors to the canton, among the main attractions are the natural and cultural, which in a process of signing will be shown globally for its assessment and tourism exploitation. This presents the opportunity to contribute to the local development of Canton Mocache, the design of registration cards of cultural and natural assets whose basis is the success of local entrepreneurs who are owners of accommodation establishments or service establishments (food) and have the opportunity to diversify income based on their activity with income generated from an offer of local tourism products and services. It is important, as a consequence, the generation of quality local jobs, higher income for families and training opportunities. It is expected to conceptualize a tourism product with sustainability principles, implemented the tourism area and by the inhabitants of the canton This proposal seeks to execute a promotion plan where tangible implementation of tourism resources will be executed and establish a dissemination agenda, which will allow the next participation in national and international fairs with the Mocache tourism brand and finally it is expected to have a positive influence on the tourist developments of the same and most importantly obtain a large influx of visitors.